2010
DOI: 10.1007/s11205-010-9752-y
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Values of Quality of Life Dimensions in Elderly People. A SEM Preference Model Approach

Abstract: Quality of life, Elderly, Preferences, Structural equation modeling, Thurstone,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 25 publications
0
17
0
2
Order By: Relevance
“…We decided to use the structural equation modelling technique-a widely used method, but so far not (or very rarely) used for analysing farmers' life quality. Similar analyses were carried out on other social groups, for example, while analysing the impacts of leisure and tourism on the elderly's quality of life in Japan [155], assessing preferences among quality of life dimensions for the elderly (people aged from 65 to 94 years old) [156], or examining the relationships between authenticity, subjective happiness, and life satisfaction [157]. As we can see, SEM can be used mainly to analyse not the life quality level, but the relationships between the elements of this concept.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We decided to use the structural equation modelling technique-a widely used method, but so far not (or very rarely) used for analysing farmers' life quality. Similar analyses were carried out on other social groups, for example, while analysing the impacts of leisure and tourism on the elderly's quality of life in Japan [155], assessing preferences among quality of life dimensions for the elderly (people aged from 65 to 94 years old) [156], or examining the relationships between authenticity, subjective happiness, and life satisfaction [157]. As we can see, SEM can be used mainly to analyse not the life quality level, but the relationships between the elements of this concept.…”
Section: Discussionmentioning
confidence: 99%
“…Mental comfort was represented by the observed variables stress and free time. Negative consequences of stress and lack of free time have been described many times in research on both mental and physical health [165,166], as well as in research on farming [61,63,102,156,167]. Also, Windon et al [48] found out that farmers' life quality was lowered mostly by stress-generating factors connected to farming (input costs, financial pressures, and cost of agricultural equipment) and lack of sleep (meaning absolutely no free time in busy season).…”
Section: Discussionmentioning
confidence: 99%
“…Participants without children more often experienced support for living a good life from PHVs than those who had children. Good social relationships and meaningful activities are among the most important aspects of positive functioning and well‐being among older people . We surmise that relationships with children and grandchildren contribute to meaningfulness and good lives.…”
Section: Discussionmentioning
confidence: 93%
“…This section presents a review of the SEM literature that has supported this research. Elosua [17] proposed a model in the framework of SEM to assess preferences among quality of life dimensions for the elderly. Likewise, the recent work of Caridad and Ocerín [18] provides clear examples of SEM using AMOS.…”
Section: Literature Reviewmentioning
confidence: 99%